Training teachers to the conditions of distance education - Shkutina, L.; Karmanova, Zh.; Mazhenova, R.; Manashova, G.; Abylaikhan, S. (KSU publ., 2015)
The problems of preparing distant teaching in the context of its future professional preparation are revealed in this article. The sphere of use on the basis of practice getting their skills is determined. The didactical supply of distant teaching is analyzed.
Keywords: training; distant teaching; distance education